Adsorption versus grafting of poly(N-Isopropylacrylamide) in aqueous conditions on the surface of cellulose nanocrystals. (15th April 2019) - Gicquel, Erwan; Martin, Céline; Heux, Laurent; Jean, Bruno; Bras, Julien
Highlights: Grafting strategy of thermo-sensitive oligomers onto Cellulose NanoCrystals (CNC). Discussion between grafting vs adsorption of the Pnipam2500 on CNC. Thermo-reversible aggregation in suspension. Thermo-sensitive behavior of hydrogel observed by rheological experiments. Abstract: This study proposes a grafting strategy of thermo-sensitive amine-terminated oligomers of Poly(N-Isopropylacrylamide) (Pnipam2500 ) onto the surface of Cellulose Nanocrystals (CNCs). Pnipam2500 grafting in aqueous condition via peptidic coupling was explored to obtain CNC hydrogel with thermo-reversible aggregation and new colloidal properties. A discussion between grafting vs adsorption /presence of the Pnipam2500 is proposed. A large range of experimental techniques was used to investigate the properties of the CNC decorated with polymer and to confirm the grafting. Elemental analysis, infrared spectroscopy, solid state NMR and conductometric titration of washed CNC-g-Pnipam2500 demonstrate that at least a part of Pnipam2500 was covalently bonded with CNC. A thermo-reversible aggregation was observed by Dynamic Light Scattering experiments and thermo-sensitive behavior is observed by rheological experiments. For grafted polymer the viscosity increases from 0.008 to 40 Pa∙s at low shear rate when the LCST is reached, whereas, in the case of polymer adsorption, the viscosity increases only from 0.002 to 0.3 Pa∙s. This thermo-reversible, bio-based and biocompatible system paves the way for the design of injectable hydrogel and biomedical nanocomposite materials.